Online education of students with mild intellectual disability and autism spectrum disorder during the COVID-19 pandemic - Buchnat, Marzena; Wojciechowska, Aneta (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2020)
The situation of the pandemic of SARS-CoV-2 virus that causes COVID-19 disease is a new and unknown situation for everyone, causing fear and uncertainty. It is also a situation that has led to numerous changes in the everyday life of many people, including students who had to adapt to the new reality of distance education from day to day. The paper concerns with the situation of online education of students with mild intellectual disability and autism spectrum disorder. It is an attempt to indicate the difficulties encountered by this group of students in the situation of distance learning from a perspective of both the student and the teacher. The paper also indicates the issues which should be considered in this education, the way of its adaptation to the possibilities of the discussed group of students, as well as elements which are really important in this education.